2014
DOI: 10.1176/appi.ajp.2013.13040574
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Voxel-Based Morphometry Mega-Analysis of Structural Brain Scans in Obsessive-Compulsive Disorder

Abstract: These findings partially support the prevailing fronto-striatal models of OCD and offer additional insights into the neuroanatomy of the disorder that were not apparent from previous smaller studies. The group-by-age interaction effects in orbitofrontal-striatal and (para)limbic brain regions may be the result of altered neuroplasticity associated with chronic compulsive behaviors, anxiety, or compensatory processes related to cognitive dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
132
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(145 citation statements)
references
References 43 publications
9
132
4
Order By: Relevance
“…A wealth of brain imaging studies aimed at examining this hypothesis and its extensions. Results moderately support the model (de Wit et al, 2014) showing volume reductions in gray and white matter of the dorso-medial prefrontal cortex, the anterior cingulate cortex, the inferior frontal gyrus, and the anterior insula. Interestingly, altered neuroplasticity with increasing age of patients was detected in this large-scale analysis, with orbitofrontal-striatal regions being more preserved in higher-aged OCD patients, and a relative loss of limbic and paralimbic regions with increasing age.…”
Section: Brain Circuitrysupporting
confidence: 62%
“…A wealth of brain imaging studies aimed at examining this hypothesis and its extensions. Results moderately support the model (de Wit et al, 2014) showing volume reductions in gray and white matter of the dorso-medial prefrontal cortex, the anterior cingulate cortex, the inferior frontal gyrus, and the anterior insula. Interestingly, altered neuroplasticity with increasing age of patients was detected in this large-scale analysis, with orbitofrontal-striatal regions being more preserved in higher-aged OCD patients, and a relative loss of limbic and paralimbic regions with increasing age.…”
Section: Brain Circuitrysupporting
confidence: 62%
“…Moreover, both structural and functional studies have found changes in the cerebellum in OCD. Recently, a multicenter VBM mega-analysis (employing 436 OCD patients and 382 HCS) revealed greater cerebellar GM volume bilaterally in OCD (de Wit et al, 2014). Moreover, Anticevic and colleagues demonstrated increased functional connectivity in the left cerebellum using whole-brain global connectivity analysis (Anticevic et al, 2014), and reduced activation in the cerebellum in patients with OCD was noted during fear conditioning (Milad et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results obtained from volumetric studies have revealed differences in both cerebral gray matter (GM) and white matter (WM), as well as specific regional abnormalities in the basal ganglia and cerebellum (de Wit et al, 2014;Hoexter et al, 2012;Szeszko et al, 2008;van den Heuvel et al, 2009). Meanwhile, a growing number of neuroimaging studies have reported evidence of functional neural abnormalities in OCD relative to HCS, pointing to the involvement of a cortico-striatal circuit in the behavioral control functions of OCD (Anticevic et al, 2014;Marsh et al, 2014;Milad et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses have also highlighted abnormalities in gray matter volume within the dorsal prefrontal-striatal model, including volume reduction in the ACC and OFC and reduced bilateral gray matter volume in the dorsomedial frontal/ACC, as well as greater volume in the thalamus and increased bilateral gray matter volume in lenticular/caudate nuclei [12,13]. Mega-analysis of neuroimaging data from six research centers indicated bilateral volume reduction in frontal gray matter, including the dorsomedial prefrontal cortex, ACC, and the inferior frontal gyrus extending to the anterior insula [14]. However, another meta-analysis reported gray matter density reduction in the dorsolateral prefrontal cortex (DLPFC), supramarginal gyrus, and OFC, as well as gray matter density increase in the putamen and anterior prefrontal cortex in OCD [15].…”
Section: Introductionmentioning
confidence: 99%